Clinical Utility of Serum Cystatin C in Predicting Diabetic Nephropathy Among Patients with Diabetes Mellitus: a Meta-Analysis - Baoqin Zhou; Honghong Zou; Gaosi Xu (Karger Publishers, 2016)
Background/Aims: Clinically, there is lack of predictors for diabetic nephropathy (DN) in diabetes mellitus (DM) without microalbuminuria, macroalbuminuria or retinopathy. Methods: PubMed, Chinese Biomedical Database, Cochrane Library, EMBASE and Elsevier Database were searched from inception to August 13, 2016. Studies involving patients with DM and containing data on cystatin C measurements and the measured glomerular filtration rate (mGFR) were included. Pooled sensitivity, specificity, positive predictive value, negative predictive value and other diagnostic indices were evaluated using a random effect model. Results: The meta-analysis enrolled 9 studies with 1417 patients. The pooled sensitivity and specificity of serum cystatin C for predicting DN were 0.88 (95% CI 0.85 - 0.91) and 0.85 (95% CI 0.82 - 0.87), respectively. The pooled positive and negative predictive values of serum cystatin C for predicting DN were 7.04 (95% CI 4.33 - 11.43) and 0.13 (95% CI 0.09 - 0.20), respectively. The area under the summary receiver operating characteristic (SROC) curve was 0.9549, and the diagnostic odds ratio was 66.80 (95% CI 27.92 - 159.86). Conclusion: Serum cystatin C is an early predictor of DN among patients with DM.